Patterning of organic photovoltaic modules by ultrafast laser. (21st September 2013) - Kubis, Peter; Li, Ning; Stubhan, Tobias; Machui, Florian; Matt, Gebhard J.; Voigt, Monika M.; Brabec, Christoph J.
Abstract In this paper, we demonstrate that laser patterning of organic solar cells by ultrafast laser systems (pulse length <350 fs) is an attractive process to produce photovoltaic modules with outstanding high geometric fill factors. Moreover, in terms of precision, registration, and debris generation and in terms of keeping the damage to the underneath layers at a minimum, ultrafast laser patterning with a pulse length of few hundreds of femtoseconds turns out to yield superior results. Ablation of all three different solar cell layers (electrodes (P1 and P3) and interfaces and semiconductor (P2)) is achieved with a single wavelength simply by a precise adjustment of the laser fluence and the patterning overlap. Camera positioning allows a precise registration between the various processing steps and a reduction of the width of the overall interconnection regime to the hundreds of micrometers dimension, resulting in high geometrical fill factors of over 90% for monolithically interconnected organic solar cell modules. Copyright © 2013 John Wiley & Sons, Ltd.